Development of mathematical apparatus of the expert system for modelling ice cream recipes with specified quality parameters - Breus, Natalia; Hrybkov, Serhii; Polishchuk, Galyna; Seidykh, Olga (My University, 2019)
As a result of the development of the expert system mathematical apparatus, a set-theoretical mathematical model of the finished product quality control at the stage of operative planning of new types of ice cream with increased nutritional value has been obtained; multi-component ice cream recipes have been optimized in terms of composition; and a model for determining the optimal set of control actions in the presence of technological defects in the calculation of recipes has been built.
Keywords: mathematical apparatus; expert system; optimization; ice cream; математичний апарат; експертні системи; оптимізація; морозиво; кафедра технології молока і молочних продуктів; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки